2022
DOI: 10.1039/d2qo00133k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of reverse glycosyl fluorides via organophotocatalytic decarboxylative fluorination of uronic acids

Abstract: An efficient protocol for organophotocatalytic synthesis of reverse glycosyl fluorides (RGFs) is established relying on 9-mesityl-10-methyl-acridinium (Mes-Acr+)-mediated oxidative decarboxylative fluorination of uronic acids. Both pentofuranoid and hexopyranoid uronic acids are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Reversed glycosyl fluorides have been synthesized by decarboxylative fluorinations of uronic acid derivatives in the presence of an acridinium photocatalyst ( Scheme 40 ). 94 Li and co-workers found that disarmed (benzoyl-protected) substrates tended to give lower yields of the reversed glycosyl fluorides than their armed, benzyl-protected counterparts. Nucleoside analogs arising from fluorination at C4′ were also accessed using this approach.…”
Section: Radicals At Non-anomeric Positions Via C–...mentioning
confidence: 99%
“…Reversed glycosyl fluorides have been synthesized by decarboxylative fluorinations of uronic acid derivatives in the presence of an acridinium photocatalyst ( Scheme 40 ). 94 Li and co-workers found that disarmed (benzoyl-protected) substrates tended to give lower yields of the reversed glycosyl fluorides than their armed, benzyl-protected counterparts. Nucleoside analogs arising from fluorination at C4′ were also accessed using this approach.…”
Section: Radicals At Non-anomeric Positions Via C–...mentioning
confidence: 99%
“…In a recent development, Li’s group established a protocol for the organophotocatalytic synthesis of glycosyl fluorides without the addition of silver species. This method relies on 9-mesityl-10-methyl-acridinium (Mes-Acr + )-mediated oxidative decarboxylative fluorination of uronic acids [ 67 ] ( Figure 10 b). The potential of this method is promising in the synthesis of fluorinated nucleosides.…”
Section: Synthesis Of Fluorine-containing Glycomimeticsmentioning
confidence: 99%
“…These methods face challenges in preparing glycosyl azides of rare sugars due to the poor accessibility of the corresponding starting sugar materials. In continuation of our interest in radical functionalization of uronic acids, we describe herein a novel approach to access structurally diverse RGAs and rare sugar-based glycosyl azides through radical decarboxylative azidation of uronic acids. The transformation is efficiently catalyzed by Ag 2 CO 3 , using K 2 S 2 O 8 as the sacrificial oxidant and 3-pyridinesulfonyl azide (3-PySO 2 N 3 ) as the azidating source.…”
mentioning
confidence: 99%
“…Building on the success of radical decarboxylative azidation of aliphatic carboxylic acids and our previous work on decarboxylative functionalization of uronic acids, we initiated our studies using glucuronic acid 4a as a model substrate. Through systematic evaluation of various reaction parameters (detailed in Supporting Information (SI), Table S1), we identified the optimal reaction conditions as follows: 4a (1.0 equiv), 3-PySO 2 N 3 5 (3.0 equiv) as azidating agent, Ag 2 CO 3 (0.15 equiv) as catalyst, K 2 S 2 O 8 (2.0 equiv) as the terminal oxidant, and stirring at 80 °C for 1 h in a mixture of MeCN/H 2 O (v/v, 1:1).…”
mentioning
confidence: 99%